Oncologic Outcomes of Total Length Gleason Pattern 4 on Biopsy in Men with Grade Group 2 Prostate Cancer. Issue 2 (1st August 2022) - Perera, Marlon; Assel, Melissa J.; Benfante, Nicole E.; Vickers, Andrew J.; Reuter, Victor E.; Carlsson, Sigrid; Laudone, Vincent; Touijer, Karim A.; Eastham, James A.; Scardino, Peter T.; Fine, Samson W.; Ehdaie, Behfar
Abstract : Purpose: Gleason Score 7 prostate cancer comprises a wide spectrum of disease risk, and precise substratification is paramount. Our group previously demonstrated that the total length of Gleason pattern (GP) 4 is a better predictor than %GP4 for adverse pathological outcomes at radical prostatectomy. We aimed to determine the association of GP4 length on prostate biopsy with post-prostatectomy oncologic outcomes. Materials and Methods: We compared 4 GP4 quantification methods—including maximum %GP4 in any single core, overall %GP4, total length GP4 (mm) across all cores and length GP4 (mm) in the highest volume core—for prediction of biochemical recurrence-free survival after radical prostatectomy using multivariable Cox proportional hazards regression. Results: A total of 457 men with grade group 2 prostate cancer on biopsy subsequently underwent radical prostatectomy. The 3-year biochemical recurrence-free survival probability was 85% (95% CI 81–88). On multivariable analysis, all 4 GP4 quantification methods were associated with biochemical recurrence—maximum %GP4 (HR=1.30; 95% CI 1.07–1.59; p=0.009), overall %GP4 (HR=1.61; 95% CI 1.21–2.15; p=0.001), total length GP4 (HR=2.48; 95% CI 1.36–4.52; p=0.003) and length GP4 in highest core (HR=1.32; 95% CI 1.11–1.57; p=0.001). However, we were unable to identify differences between methods of quantification with a relatively low event rate. Conclusions: These findings support further studies on GP4 quantification in addition to the ratio of GP3 and GP4 to classify prostate cancer risk. Research should also be conducted on whether GP4 quantification could provide a surrogate endpoint for disease progression for trials in active surveillance.